PENGEMBANGAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN TOLERANSI SISWA SEKOLAH DASAR - Sani Elfajira; Ahmad Mulyadiprana; Tb. Moh. Irma Ari Irawan (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT Amid the increasing challenges of social, cultural, and religious diversity in Indonesia, fostering tolerance among elementary school students has become an urgent necessity that must be supported by appropriate learning media. However, systematic studies examining the effectiveness of learning media in the context of tolerance education remain limited, particularly regarding flipbook media, which have been less frequently investigated compared to other forms of media. This study aims to examine the effectiveness of various learning media in promoting tolerance through a systematic literature review (SLR) method. The literature was collected from the Google Scholar and Garuda databases using relevant keywords and subsequently screened based on inclusion and exclusion criteria. Out of 50 articles initially identified, 11 articles met the criteria and were selected for analysis. The findings indicate that media such as videos, pop-up books, podcasts, and posters are effective in enhancing students' understanding of and attitudes toward tolerance. Flipbooks based on local wisdom were also found to be feasible and practical; however, research on this medium remains very limited compared to other types of media. These findings provide practical contributions for teachers in selecting relevant instructional media, while also highlighting opportunities for further research on flipbooks as an innovative character education medium aligned with the implementation of the Merdeka Curriculum. ABSTRAK Di tengah meningkatnya tantangan keberagaman sosial, budaya, dan agama di Indonesia, penanaman sikap toleransi pada siswa sekolah dasar menjadi kebutuhan mendesak yang harus didukung oleh media pembelajaran yang tepat. Namun, kajian sistematis mengenai efektivitas media dalam konteks pendidikan toleransi masih terbatas, terutama untuk media flipbook yang jarang diteliti dibandingkan media lain. Penelitian ini bertujuan menelaah efektivitas berbagai media pembelajaran dalam menumbuhkan sikap toleransi melalui metode systematic literature review (SLR). Literatur dikumpulkan dari database Google Scholar dan Garuda dengan kata kunci relevan, kemudian diseleksi berdasarkan kriteria inklusi dan eksklusi. Dari 50 artikel yang ditemukan, sehingga diperoleh 30 artikel dari 50 artikel awal untuk dianalisis. Hasil kajian menunjukkan bahwa media seperti video, pop-up book, podcast, dan poster terbukti efektif meningkatkan pemahaman dan sikap toleransi siswa. Flipbook berbasis kearifan lokal juga dinilai layak dan praktis, namun penelitiannya masih sangat terbatas dibandingkan media lain. Temuan ini memberikan kontribusi praktis bagi guru dalam memilih media yang relevan, sekaligus membuka peluang penelitian lanjutan mengenai flipbook sebagai inovasi media pembelajaran karakter yang sesuai dengan implementasi Kurikulum Merdeka.